EFEKTIVITAS PEMBELAJARAN DENGAN MEDIA DIORAMA BERBASIS KEARIFAN LOKAL SUBTEMA KEUNIKAN DAERAH TEMPAT TINGGALKU KELAS IV SDN PANDANAN - Lia Rohmawati; Arya Setya Nugroho (JUSEDA, 2020)
This study aims to determine the effectiveness of local wisdom based diorama media on the subtheme of the uniqueness of the area where I live class IV SDN Pandanan. The subject of this study in Pandanan Elementary School with 16 students consisting of 13 men and 3 women. Data collection methods used are observation methods, and test methods. While the research instrument uses teacher activity observation sheets, student activity observation sheets and learning achievement test sheets in order to find out student learning outcomes. The results of the teacher's ability to manage learning reached very good criteria, because in the whole meeting had an average of 93.7 which was in the scale of 85-100 which was included in the excellent category. Student activities are included in the active category which reaches 63.35% of the percentage that must be achieved ≥ 50%. The learning achievement test reaches 87.5% and is said to be complete if the classical completeness is at least ≥75%. Then it can be concluded that the diorama media can be used as a learning support medium.